Evaluating Trend of Physical Urban Expansion of Shiraz City and physiographic conditions effect on land use changes - M. Morovati; F. Falahati; M. Darvishi; S.M. Monavari; Z. Rousta (جغرافیا و برنامه‌ریزی محیطی, 2013)
Extended abstract1- IntroductionNatural environment hasn’t permanently adjusted with urban expansion and human settlements. Many historical cities have been abandoned due to these Natural environment incompatibilities. The most effective factors of natural environment on urban expansion are topography, slope, weather, geology, hydrology and geomorphology conditions. By increasing of trend urbanization, cities need to vast territories for settling the population, these territories have composed of different topographic and geomorphologic units. The impact of growth rate of city size on topographic and geomorphologic units will be complicated, by increasing of urban expansion. Orientation of physical expansion in terms of effective factors must be in a way that less damages imposes on natural environment and can be preserved environment in a direction of preservation of sustainable Development. Changes in the earth’s surface can be related to natural dynamics or human activities and can occur either suddenly or gradually. Accelerated urban growth is usually associated with and driven by the population concentration in an area. The extent of urbanization or its growth drives the change in land use/cover pattern. Land use and land cover changes may have adverse impacts on ecology of the area, specially hydro-geomorphology and vegetation. As the characteristics of land cover have important impacts on climate, biogeochemistry, hydrology and species diversity, land cover change has been indicated as one of the high priority concerns for research and for the development of strategies for sustainable management. Although urban areas currently cover only 3% of the Earth’s land surface, they have marked effects on environmental conditions at both local and global scales, including climate change.2- MethodologyRecently, remote sensing has been used in combination with Geographical Information Systems (GIS) and Global Positioning Systems to assess land cover change more effectively than by remote sensing data only. This paper presents an integrated study of land use/cover changes and urban expansion in Shiraz city, Fars province in Iran. The study explores the temporal and spatial characteristics of urban expansion and land use/cover changes from 1990 to 2009. Statistical classification approaches have been used for the classification of the remotely sensed images obtained from various sensors viz. Landsat TM, ETM+ and IRS PAN, LISS-III.3– DiscussionLand use/land cover changes (LUCC) are major cause of ecological environmental changes. Geometric correction was performed on all the images. At least 17 ground control points (GCPs) were used to register the images UTM zone 39. GCPs were dispersed throughout the scene, yielding a RMS error was around 0.2 pixels. Geospatial data including municipal boundaries, road networks, geomorphic units and elevation units (DEM) were used to produce GIS layers by ArcGIS 9.3. The most useful band combinations in Landsat for discrimination of land cover categories are bands 4-5-3, 4-3-2, and 3-2-1 assigned as red, green, and blue, respectively. All satellite data were studied using spectral and spatial profiles to ascertain the digital numbers (DNs) of different LULC categories prior to classification. Finally, classification has been done using the Knowledge Classifier Module of ERDAS.4– ConclusionFinally classification, five land cover categories exist in this area: (a) urban or built-up land; (b) agriculture; (c) water, (d) orchard, and (e) bare land. Results indicate that cropland, water, and orchard areas reduced by 37.8%, 5.8%and 45.7% continuously over the past 19 years, while built-up area increased by 37%, respectively. The built-up area increased at the cost of decreased cropland, water and orchard. Lastly, the major factors influencing urban expansion and land use/cover change are also discussed. In general, the population, traffic conditions, industrialization, and policy are the major factors that influenced the urban expansion.Key words: Land use change, Physiographic qualification, Urban expansion, Remote sensing, GISReferencesAlavipanah, seyed kazem, (2003), Application of remote sensing in the earth sciences(soil), Tehran university publisher.Alig, R.J., Kline, J.D., Lichtenstein, M, (2004) Urbanization on the US landscape: looking ahead in the 21st century. Landscape Urban. Plann. 69, 219–234.Bozorgnia, farnaz, (2007), Urban schematization by using GIS (study area, Lenjan), The first conference of urban GIS, shomal university,Amol.Breheny, M. (1992). Sustainable Development and Urban Form, Pion, London.CEC Commission of European Communities). 1990). Green Paper on the Urban Environment, COM 90218, CEC, Brussels.Christopher A. Legg, (1999), Remote Sensing and Geographic Information Systems: Geological Mapping, Mineral Exploitation and Mining, John Wiley & Sons, Published association with Praxis Publishing Chichester.Elkin, T, et al. (1991). Receiving the City: Towards Sustainable Urban evelopment, Friends of the Erath, London.Fatemi, B. & Rezaie, Y. (2005), Fundamental remote sensing, Azade publisher.Gharagozlu, A. (2004), GIS & Evaluation & Environmental planning, Topography organization publisher. He. C., Okada. N, Zhang. Q., Shi. P., Zhang. J. (2006), Modeling urban expansion scenarios by coupling cellular automata model and system dynamic model in Beijing, China, Applied Geography 26: 323–345.http://www. glcf.umiacs.umd.edu/http://www.leica geosystems.com/corporate/en/monitoring/11855.htm Jenks, M, Burton, E and Williams, K. (1996). The Compact City: A Sustainable Urban Form, E and FN Spon, an imprint of Chapman and Hall, London. Jensen, J. R.,(1996), Introductory Digital Image Processing: A remote sensing perspective, 2nd Edition. NJ: Prentice-Hall.Leica-geosystems Website (2008) at: Li, X, Yeh, A.G.O, (1998). Principal component analysis of stacked multitemporal images for the monitoring of rapid urban expansion in the Pearl River Delta. Int. J. Remote Sens. 19, 1501–1518.Makhdoum, M etal, (2004), Environmental evaluation and planning by geographic information system, Tehran university puplisher.Makhdoum, M, (2001), Fundamental of landuse planning, Tehran university puplisher.Malmiran, Hamid, (2001) Digital processing of satellite images, National geographical organization poblisher.NGDIR Website (2007) at: http://www.ngdir.ir/Papers/PPapersDetail.asp?PID=135988S. Berberoglu, A. Akin, (2009), Assessing different remote sensing techniques to detect land use/cover changes in the eastern Mediterranean, International Journal of Applied Earth Observation and Geoinformation, 11, 46-53.Tabibian, M. & Dadrast, M. (2004) Supervision of landuse changes in Drough zan, Fars province by using GIS & RS, Mohit shenasy journal, No 29, P 79-91.Tarek.Rashed, Carsten.Jürgens, (2010), Remote Sensing of Urban and Suburban Areas, Springer.Timothy L. Nyerges, Piotr Jankowski (2009). Regional and Urban GIS: A Decision Support Approach, The Guilford Press.USGS Website (2008) at: http://geochange.er.usgs.gov/sw/changes/anthropogenic/population/las_ vegas.htmWu. Q., Li. H., Wang. R., Paulussen. J., He. Y., Wang. M., Wang. B., Wang. Z. (2006), Monitoring and predicting land use change in Beijing using remote sensing and GIS. Landscape and Urban Planning. 78, 322–33. Zhang, J., Zhang, Y. (2007), Remote sensing research issues of the National Land Use Change Program of China. ISPRS Journal of Photogrammetry & Remote Sensing, doi:10.1016/j.isprsjprs.2007.07.002.Zhenjiang Shen,(2009), Geospatial Techniques in Urban Planning, Springer.Zobeiry, M. & Majd, Alireza. (2004), An introduction to remote sensing technology and its application in natural resources. Tehran university puplisher, sixth edition.